Implementation of an E-Commerce Platform for Commercial Management in Companies dedicated to the Marketing of Household Appliances - BRAVO HUIVIN, ELIZABETH KRISTINA; De La Rosa-Mendoza, Luis Angel; Rios-Diaz, Juan Jose (LACCEI, 2024)
The present study concerns the implementation of an E-commerce platform to improve commercial management in a Mype company dedicated to the marketing of household appliances in the city of Chepén, Peru. A pre-experimental research approach was used, where data collection techniques such as survey, interview and documentary analysis were used, which were applied to 4 business processes and 79 clients of the company under study. For the implementation of the online store, the AGILE methodology was applied, which presents the following stages, Stage 1: Company Evaluation, Stage 2: Improvement Suggestions, Stage 3: Design and Implementation of the solution, Stage 4: Evaluation and Monitoring. From the implementation it is concluded that the E-Commerce platform had a positive impact on commercial management, increasing the percentage of online sales by 251%, increasing the average purchase ticket by S/. 50.29, achieving greater customer loyalty by 14.29%, reducing the cart abandonment percentage by 6%, among others. The article is described in introduction, state of the art, objectives, material and methods, methodology for the implementation of E-Commerce, results, discussions and conclusions.